1994
DOI: 10.1212/wnl.44.3_part_1.481
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 infection of subcortical astrocytes in the pediatric central nervous system

Abstract: Early reports of pediatric HIV-1-associated neuropathology described the presence of viral particles in some astrocytes, implicating direct infection of the immature nervous system as a contributing factor to the observed neuropathology. Several recent reports suggest that in those astrocytes infected with HIV-1, the level of antigenic expression of the proviral genome is below the sensitivity limits of conventional histochemical techniques. Identification of these astrocytes would instead require the use of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
206
1
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(216 citation statements)
references
References 0 publications
7
206
1
2
Order By: Relevance
“…Since HIV-1 infection of astrocytes is limited, persisting for prolonged periods in a low productive and non-cytolytic state (Shahabuddin et al, 1992;Tornatore et al, 1991Tornatore et al, , 1994a, these results suggest that the parallel e ects observed following infection with HIV-1 and gp120 treatment may re¯ect gene changes resulting as a consequence of signaling events mediated by cell surface interactions. The dysregulation in cellular gene expression may be one route through which HIV-1 infected astrocytes contribute to HAD, despite relatively ine cient viral expression.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Since HIV-1 infection of astrocytes is limited, persisting for prolonged periods in a low productive and non-cytolytic state (Shahabuddin et al, 1992;Tornatore et al, 1991Tornatore et al, , 1994a, these results suggest that the parallel e ects observed following infection with HIV-1 and gp120 treatment may re¯ect gene changes resulting as a consequence of signaling events mediated by cell surface interactions. The dysregulation in cellular gene expression may be one route through which HIV-1 infected astrocytes contribute to HAD, despite relatively ine cient viral expression.…”
Section: Discussionmentioning
confidence: 92%
“…Astrocytes also can be infected with HIV-1 in vitro and in vivo, although with lower e ciency than T cells and macrophages (Dewhurst et al, 1987;Saito et al, 1994;Tornatore et al, 1991Tornatore et al, , 1994areviewed in BrackWerner, 1999). The limited infection of astrocytes has been attributed to various mechanisms, including intracellular restrictions to virus expression (Gorry et al, 1999;Ludwig et al, 1999;Tornatore et al, 1994b) or, as we have shown recently, ine cient virus entry (Bencheikh et al, 1999;Canki et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent morphometric study found a statistically significant reduction in the volume of all cortical regions, most of the subcortical gray matter (e.g., caudate nucleus, putamen, globus pallidus, claustrum, and thalamus), and in cerebral white matter [5]. In addition, HIV-1 infection restricted to the production of regulatory gene products in astrocytes has been reported [6,7]. Other prominent pathological findings include widespread activation of microglia, reactive astrocytosis [4], and evidence of neuronal loss and damage to the dendritic arbor [8][9][10][11].…”
mentioning
confidence: 99%
“…In the brain, microglia/macrophage are the primary targets of HIV-1 infection (128), but in vivo infection of astrocytes has been documented in multiple studies (129)(130)(131)(132)(133)(134)(135)(136). Astrocytes present an abundant CNS target, but the course of infection is generally a long-term latent process.…”
Section: Impairment Of Astrocytes In Hadmentioning
confidence: 99%